2003
DOI: 10.1034/j.1600-0625.12.s2.4.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of changes in stratum corneum keratin in wrinkle formation by chronic ultraviolet irradiation in hairless mice

Abstract: Chronic exposure to ultraviolet (UV) radiation alters components of the skin. We previously reported that chronic low-dose UV irradiation induced wrinkle formation but did not significantly alter dermal components of hairless mice. In the present study, we examined whether the epidermal changes by UV irradiation could contribute to wrinkle formation. Hairless mice were irradiated with one-third the minimum erythema dose (MED) of UVB (20 mJ/cm2) and UVA (14 J/cm2) for 10 weeks, and followed up for another 24wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
3
29
0
1
Order By: Relevance
“…Previous studies in animal models indicate the cause effect relationship between repetitive UV irradiation and an increase of keratins K1, K5, and K10, with no changes in the collagen fibers and elastic fibers, resulting in loss of skin elasticity and the formation of skin wrinkles. 12,13 Conversely, in our study, repeated UVB irradiation stimulated a stable expression of keratins K6 and its partners K16 and K17, but not K1, K5, and K10. Keratins K6, K16, and/or K17, which are not usually expressed in the innate state of normal epidermis, have been reported to initially induce in the suprabasal layers as early as 6 hours after injury or during the first 24 to 48 hours of UVB irradiation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Previous studies in animal models indicate the cause effect relationship between repetitive UV irradiation and an increase of keratins K1, K5, and K10, with no changes in the collagen fibers and elastic fibers, resulting in loss of skin elasticity and the formation of skin wrinkles. 12,13 Conversely, in our study, repeated UVB irradiation stimulated a stable expression of keratins K6 and its partners K16 and K17, but not K1, K5, and K10. Keratins K6, K16, and/or K17, which are not usually expressed in the innate state of normal epidermis, have been reported to initially induce in the suprabasal layers as early as 6 hours after injury or during the first 24 to 48 hours of UVB irradiation.…”
Section: Discussionmentioning
confidence: 77%
“…[1][2][3] Skin photodamage is physiologically correlated with several alterations including the increase and disorganization of elastic fibers and the reduction of collagens in the dermal extracellular matrix 4 -11 and the increase of keratin contents and the deterioration of keratin intermediate filaments (KIFs) in the epidermis. [12][13][14] Elastic fibers are age-dependent-decreasing dermal extracellular matrix that respond primarily to the fibrous mechanism controlling cutaneous elasticity. 4,5,15,16 The accumulation of dystrophic elastotic material in the reticular dermis, referred to as solar elastosis, is commonly observed in photoaged skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vivo studies have shown that UVB radiation affects epidermal morphology, including increasing the mean SC thickness (12), and disrupts the permeability barrier, causing morphological changes in SC lipids, increased transepidermal water loss, and decreased SC hydration (13,14). Surprisingly, to our knowledge, no studies have explored how UV exposure affects the mechanical barrier function of SC.…”
mentioning
confidence: 85%
“…29 UVB also alters skin lipid composition and enzyme metabolism, 30,31 increasing transepidermal water loss. 31,32 These events culminate in premature aging of the skin, such as actinic elastosis.…”
Section: "A Tan Will Protect Me From Skin Cancer"mentioning
confidence: 99%